Development of single-step bioconversion process for bioethanol production by fungi and yeast using oil palm empty fruit bunches - Alam, Md. Zahangir (2006)
The bioethanol production was conducted by utilizing oil palm industrial solid waste, empty fruit bunches (EFB) with the treatment of mixed culture of fungi and yeast in solid state bioconversion process. The compatibility of several fungal and yeast, Saccharomyces cerevisiae were tested as to develop direct solid state bioconversion using the potential mixed culture. The mixed culture of T. harzianum and yeast has found to be the most potential as they produced 14.2 % (v/v) of ethanol among the other combination of mixed culture in liquid-broth fermentation for compatibility test. The development of single-step bioconversion applying several potential fungal-yeast mixed cultures was designed as to find out the most potential mixed culture using EFB in solid-state bioconversion (SSB). Analysis such as ethanol estimation, reducing sugar and glucosamine as growth indicator, were carried out in the experiment. The ethanol production using the compatible mixed culture of T. harzianum and yeast has resulted in 15.1 % (v/v) of ethanol in 8 days of fermentation.